Advanced Sulfur-Silicon Full Cell Architecture for Lithium Ion Batteries - Ye, Rachel (Sci Rep, 2017)
Lithium-ion batteries are crucial to the future of energy storage. However, the energy density of current lithium-ion batteries is insufficient for future applications. Sulfur cathodes and silicon anodes have garnered a lot of attention in the field due their high capacity potential. Although recent developments in sulfur and silicon electrodes show exciting results in half cell formats, neither electrode can act as a lithium source when put together into a full cell format. Current methods toward incorporating lithium in sulfur-silicon full cells involves prelithiating silicon or using lithium sulfide. These methods however, complicate material processing and creates safety hazards. Herein, we present a novel full cell battery architecture that bypasses the issues associated with current methods. This battery architecture gradually integrates controlled amounts of pure lithium into the system by allowing lithium the access to external circuit. A high specific energy density of 350 Wh/kg after 250 cycles at C/10 was achieved using this method. This work should pave the way for future researches into sulfur-silicon full cells.